2023
DOI: 10.3390/buildings13020490
|View full text |Cite
|
Sign up to set email alerts
|

Retention over Attraction: A Review of Women’s Experiences in the Australian Construction Industry; Challenges and Solutions

Abstract: Despite substantial investments and efforts by governments, construction organisations, and researchers, the construction industry remains one of the most male-dominated industries in Australia, with women being underrepresented numerically and hierarchically. Efforts to attract and retain women in construction have been implemented inconsistently on an ad hoc basis. As part of a larger research project that focuses on retaining women in the Australian construction industry, this research conducts a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…SLR helps to provide a comprehensive overview of the literature and identify gaps. There are limited studies carried in the area of women in construction; this is validated by Ghanbaripour et al (2023) research where they found that though women's participation is stubbornly low in the Australian construction industry only a limited empirical construction management literature is found on women in construction. Analysis performed on identified literature set a good groundwork to understand the construction industry scenario, the gender diversity across countries and helped to identify barriers/challenges and strategies to improve the well-being, safety, and health of women professionals at project sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLR helps to provide a comprehensive overview of the literature and identify gaps. There are limited studies carried in the area of women in construction; this is validated by Ghanbaripour et al (2023) research where they found that though women's participation is stubbornly low in the Australian construction industry only a limited empirical construction management literature is found on women in construction. Analysis performed on identified literature set a good groundwork to understand the construction industry scenario, the gender diversity across countries and helped to identify barriers/challenges and strategies to improve the well-being, safety, and health of women professionals at project sites.…”
Section: Methodsmentioning
confidence: 99%
“…Promoting an inclusive culture within construction project sites may be accomplished via actions such as targeted recruitment drives, diversity training, and mentoring programmes (Vohra et al, 2015). Ghanbaripour et al (2023) found that women professionals benefit from specialised training programmes that address their particular needs and difficulties faced at construction project sites. Providing clean, hygienic, and exclusive washrooms and appropriate sanitary facilities at project sites contributes to the well-being of women (Griffin, 2013).…”
Section: Strategiesmentioning
confidence: 99%
“…In contrast, a weak organizational culture of gender diversity would hinder the successful implementation of policies, as the company would need to depend on rules and regulations to direct employees' behavior, leading to a gap between intentions and actual practices within the organization. As stated in a recent review conducted by Ghanbaripour, Tumpa, Sunindijo, Zhang, Yousefian, Camozzi, Hon, Talebian, Liu and Hemmati [23], women perceived that they were receiving a lack of organizational support and career opportunities in construction. Future studies are recommended to investigate the factors that contribute to a strong organizational culture in gender diversity.…”
Section: Theme 2: Inclusive and Anti-discriminatory Culturementioning
confidence: 99%
“…The findings revealed that there were fewer initiatives focusing on providing adequate support and resources for work-life balance. A previous study highlighted the difficulties in achieving work-life balance as a significant challenge for women in the construction industry, which negatively impacts their career advancement and their willingness to stay in the industry [23]. It was found that flexible working hours were often offered for specific roles and positions, sometimes not available to women.…”
Section: Theme 6: Flexible Working Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation